Bioprinting on 3D Printed Titanium Scaffolds for Periodontal Ligament Regeneration - Ui-Lyong Lee; Seokhwan Yun; Hua-Lian Cao; Geunseon Ahn; Jin-Hyung Shim; Su-Heon Woo; Pill-Hoon Choung (Cells, 2021)
The three-dimensional (3D) cell-printing technique has been identified as a new biofabrication platform because of its ability to locate living cells in pre-defined spatial locations with scaffolds and various growth factors. Osseointegrated dental implants have been regarded as very reliable and have long-term reliability. However, host defense mechanisms against infections and micro-movements have been known to be impaired around a dental implant because of the lack of a periodontal ligament. In this study, we fabricated a hybrid artificial organ with a periodontal ligament on the surface of titanium using 3D printing technology. CEMP-1, a known cementogenic factor, was enhanced in vitro. In animal experiments, when the hybrid artificial organ was transplanted to the calvarial defect model, it was observed that the amount of connective tissue increased. 3D-printed hybrid artificial organs can be used with dental implants, establishing physiological tooth functions, including the ability to react to mechanical stimuli and the ability to resist infections.